Rituximab maintenance versus observation following abbreviated induction with chemoimmunotherapy in elderly patients with previously untreated chronic lymphocytic leukaemia (CLL 2007 SA): an open-label, randomised phase 3 study. Issue 2 (February 2018) - Dartigeas, Caroline; Van Den Neste, Eric; Léger, Julie; Maisonneuve, Hervé; Berthou, Christian; Dilhuydy, Marie-Sarah; De Guibert, Sophie; Leprêtre, Stéphane; Béné, Marie C; Nguyen-Khac, Florence; Letestu, Rémi; Cymbalista, Florence; et al.
Summary: Background: Most patients with chronic lymphocytic leukaemia relapse after initial therapy combining chemotherapy with rituximab. We assessed the efficacy and safety of rituximab maintenance treatment versus observation for elderly patients in remission after front-line abbreviated induction by fludarabine, cyclophosphamide, and rituximab (FCR). Methods: This randomised, open-label, multicentre phase 3 trial at 89 centres in France enrolled treatment-naive and fit patients aged 65 years or older with chronic lymphocytic leukaemia without del(17p). Eligible patients had an Eastern Cooperative Oncology Group performance status of 0–1 and adequate renal and hepatic function. Patients in response to complete induction treatment with four monthly courses of full-dose FCR with two interim rituximab doses on day 14 of cycles 1 and 2 (oral fludarabine [40 mg/m 2 per day] and oral cyclophosphamide [250 mg/m 2 per day] for the first 3 days of each cycle, rituximab at 375 mg/m 2 intravenously on day 0 of cycle 1 and subsequently at 500 mg/m 2 on day 14 of cycle 1, days 1 and 14 of cycle 2, and day 1 of cycles 3 and 4) were eligible for randomisation. Recovery from FCR toxicity and patient willingness to continue the trial were mandatory. We randomly assigned (1:1) patients to either receive intravenous rituximab (500 mg/m 2 ) every 8 weeks for up to 2 years or undergo observation, with a central computer-generated randomisation list using randomly permuted blocks of variable sizes. Randomisation was stratified by IGHV mutational status, the presence or absence of del(11q), and response level to induction treatment. The primary endpoint was progression-free survival, with the objective to assess the superiority of rituximab maintenance relative to observation. The final analysis was done in the intention-to-treat population. Safety was analysed in all patients who received at least one dose of study drug in the rituximab group and in all patients in the observation group. This trial is closed to accrual whilst continuing patient follow-up. The study is registered withClinicalTrials.gov, numberNCT00645606 . Findings: Between Dec 14, 2007, and Feb 18, 2014, 542 patients were enrolled, of whom 525 started FCR induction. Between June 10, 2008, and Aug 14, 2014, 409 (78%) patients were randomly assigned to rituximab maintenance (n=202) or observation (n=207). Four (2%) patients in the rituximab group did not receive the allocated treatment (progressive disease [n=1], adverse events [n=3]). After a median follow-up of 47·7 months (IQR 30·4–65·8), median progression-free survival in the rituximab group (59·3 months, 95% CI 49·6–not estimable) was improved compared with the observation group (49·0 months, 39·9–60·5; hazard ratio 0·55, 95% CI 0·40–0·75; p=0·0002). Neutropenia and grade 3–4 infections were more common with rituximab maintenance (105 [53%] of 198 patients vs 74 [36%] of 207 patients and 38 [19%] vs 21 [10%], respectively) during the study. The most common grade 3–4 infection was lower respiratory tract infection (24 [12%] vs eight [4%]). The incidence of second cancers, except basal cell carcinoma, was similar in both groups (29 [15%] vs 23 [11%]). Deaths were related to adverse events for 23 (11%) patients in the rituximab group and 16 (8%) in the observation group. Interpretation: 2-year maintenance rituximab in selected elderly patients improves progression-free survival and shows an acceptable safety profile. Immunotherapy maintenance strategy is a relevant option in front-line treatment of chronic lymphocytic leukaemia, even in the age of targeted therapy. Funding: French National Cancer Institute (INCa), Roche, Chugai.